ANALISIS KEMAMPUAN METAKOGNISI MAHASISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DI PRODI PENDIDIKAN MATEMATIKA UNIVERSITAS TIMOR (Jurnal Karya Pendidikan Matematika, 2023)
Qualitative descriptive research that aims to analyze students' metacognition ability in solving mathematical problems. The three components of metacognition ability to be measured are developing a strategy or action plan, monitoring actions and evaluating actions. The data in this study was obtained from problem-solving test sheets, metacognition questionnaires and guidelines for interviews. The subjects in this study were students in semester 1 of the mathematics education study program for the 2022/2023 academic year by taking 3 students representing high, medium, and low ability groups. Based on the results of the study, it was obtained that students with high abilities can solve mathematical problem solving test questions because they already involve 3 components of metacognition ability very well, namely compiling action plans, monitoring actions and evaluating actions, students with moderate abilities have not been able to solve mathematical problem solving test questions because they have not evaluated actions so that there are still wrong final answers even though students Having the ability to strategize actions and monitor good actions, students with low abilities cannot complete mathematical problem solving tests because they have not been able to carry out action plans, monitor actions, and evaluate actions properly.